Penentuan Jurusan Siswa Sekolah Menengah Atas menggunakan Metode Fuzzy Tsukamoto - Hikmah Quddustiani; Ummi Athiyah; Made Riza Kartika; Rayhan Hidayat; Luthfi Rakan Nabila (Research Group of Data Engineering, Faculty of Informatics, 2021)
According to the Regulation of the Minister of National Education (Permendiknas) Number 22 of 2006, the determination of majors is carried out at the end of the second semester of class X and the implementation of Teaching and Learning Activities (KBM) according to the program majors starts in the first semester of class XI. In fact, there are still many high school students who are confused about choosing a major in a tertiary institution and this phenomenon can be seen in high school students. There are several majors in high school programs such as Natural Sciences (IPA), Social Sciences (IPS), and Language. This research is expected to be able to determine the majors according to the abilities of the new students for the process of selecting majors and provide recommendations that help students in determining the majors in SMA using the Fuzzy Tsukamoto method. The Tsukamoto method is an extension of monotonous reasoning. In the Tsukamoto method, each consequence of the IF-THEN rules must be represented by a fuzzy set with monotonous membership functions assisted by system design using the programming language PHP, HTML, Javascript, and MySQL database, resulting in a decision making system using the fuzzy method. tsukamoto which is a useful website for determining student majors so that it can lighten the work of the school in order to help speed up and make it easier for schools to make decisions in choosing majors.